TUMBUHAN MANGROVE DI KAWASAN KAKENAUWE, PULAU BUTON, SULAWESI TENGGARA : KEANEKARAGAMAN, STATUS KELANGKAAN DAN POTENSI - Hartini, Sri (Fakultas Matematika dan ilmu pengetahuan Alam. Universitas Pakuan.)
Inventory of mangroves on the island of Buton, Southeast Sulawesi was conducted in June 2010. The method used in this research is exploratory. Based on the results recorded 21 species of mangroves spread Kakenauwe region. Twelve species of them are included in the category of rare plants refers to the IUCN 2014 which Sonneratia ovata (Near threatened), Acanthus ilicifolius (Least Concern), Acrostichum aureum (Least Concern), Aegiceras corniculatum (Least Concern), Allophylus cobbe (Least Concern, ) Avicennia marina (Least Concern), Ceriops tagal (Least Concern), Cordiasebestena (Least Concern), Nypa fruticans (Least Concern), Pongamia pinnata (Least Concern), Rhizophora mucronata (Least Concern), and Xylocarpus moluccensis (Least Concern) . Ceriops tagal, Rhizophora mucronata, Bruguiera gymnorrhiza and Sonneratia ovata is a species that is often found at that location. Most of the mangrove plant species have the potential, ie as an ornamental plant, traditional medicine, foodstuff, as well as producing high-quality wood.